Antioxidant carbon aerogel material and preparation method thereof

By preparing SiC-Zr/Si-SiO2 composite coating on carbon aerogel materials, the problem that carbon aerogel materials are easily oxidized in high-temperature oxidizing atmospheres is solved, and its antioxidant properties are significantly improved, so that they have better stability and durability in high-temperature environments.

CN119660710AActive Publication Date: 2025-03-21AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH

Patent Information

Application Number
CN202411846797.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing carbon aerogel materials are easily oxidized in high-temperature oxidative atmospheres, resulting in insufficient stability and durability in engineering applications. Especially in environments above 1800°C, their oxidation resistance is insufficient to meet application needs.

Method used

Borosilicon modified phenolic resin is used as an organic precursor to prepare a borosilicon modified phenolic aerogel through an esterification reaction, and carbonize it in an inert atmosphere to form a borosilicon modified carbon aerogel. Then, SiC-Zr/Si-SiO2 composite coating is prepared on its surface by supercritical deposition technology and sol-gel method to achieve double protection effect.

Benefits of technology

It significantly improves the antioxidant properties of carbon aerogel materials, so that they can effectively protect in high temperature environments above 2200℃, extend the service life of the materials, and are suitable for different service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189431330000131
    Figure BDA0005189431330000131
  • Figure BDA0005189431330000141
    Figure BDA0005189431330000141
  • Figure BDA0005189431330000151
    Figure BDA0005189431330000151
Patent Text Reader

Abstract

The invention discloses an antioxidant carbon aerogel material and a preparation method thereof. The method comprises the following steps: sequentially adding a solvent, a boron-containing modifier and a silicon-containing modifier into phenolic resin for esterification reaction; sequentially curing, drying and carbonizing to obtain boron-silicon modified carbon aerogel; depositing a SiC inner coating on the boron-silicon modified carbon aerogel under the assistance of supercritical CO2; a Zr-Si ceramic oxygen barrier layer and a SiO2 sealing and filling layer are sequentially prepared through a sol-gel method, and the carbon aerogel material with the SiC-Zr / Si-SiO2 composite coating is prepared. The invention also provides the aerogel material prepared by the method, the oxidation resistance of the aerogel material is obviously improved, and the aerogel material can be used for preparing a thermal insulation material applied to the field of high-temperature thermal protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon aerogel materials, and in particular relates to an oxidation-resistant carbon aerogel material and a preparation method thereof. Background Art

[0002] Carbon materials have the characteristics of high specific strength, good high-temperature mechanical properties, high thermal conductivity, small thermal expansion coefficient, and excellent thermal shock resistance, and are widely used in high-temperature thermal insulation, industrial and civilian fields. Porous carbon materials, such as carbon aerogel materials, have significant advantages such as high specific surface area, low thermal conductivity, and ultra-high temperature resistance (under inert atmosphere, it can maintain a good pore structure above 2000°C), and are an ideal thermal insulation material system in the field of high-temperature thermal protection.

[0003] However, carbon materials begin to oxidize at 450°C in air, and the oxidation rate increases with the increase of oxidation temperature. Especially for carbon aerogel, its nanoporous structure, high porosity, and high specific surface area will intensify the high-temperature oxidation process of carbon materials in an aerobic environment, which will limit the engineering application of such materials to a greater extent. Therefore, ensuring the stable and long-lasting anti-oxidation of carbon aerogel materials has become a prerequisite for fully utilizing their performance.

[0004] At present, there are two main ways to improve the high-temperature oxidation resistance of carbon aerogel materials: one is to modify the material matrix to resist oxidation; the other is to protect it with antioxidant coating technology. The matrix antioxidant modification technology is an internal modification technology that passesivates the matrix itself by modifying the material's own components. The coating antioxidant modification technology is to prepare an antioxidant coating on the surface of the carbon aerogel material to isolate the material from direct contact with the oxidizing atmosphere, and improve the antioxidant performance of the carbon aerogel material at a higher temperature, so that the carbon aerogel material can still maintain its excellent performance in a high-temperature oxidizing atmosphere and expand its scope of use.

[0005] CN105646007A discloses a method for preparing a medium-low temperature and long-term anti-oxidation coating on the surface of a carbon / carbon composite material. A SiC / B4C-B2O3-SiO2-Al2O3 medium-low temperature and long-term anti-oxidation coating is prepared on the surface of a carbon / carbon composite material by a chemical vapor deposition process combined with a brushing-sintering process. The prepared coating achieves long-term anti-oxidation of the carbon / carbon composite material at 600-1000°C. CN116375504A invented a dense high-temperature anti-oxidation coating on the surface of a carbon-based or ceramic-based composite material and a preparation method thereof. By introducing a certain amount of kyanite into the coating slurry, kyanite undergoes a phase transformation to form mullite during the high-temperature sintering process. The volume expansion accompanying the phase transformation of kyanite can effectively heal the pores and microcracks in the coating, improve the density of the coating, and provide good oxidation protection for the base material at above 1200°C. CN116082065A discloses a method for improving the sintering density of an anti-oxidation coating on the surface of a carbon-based or ceramic-based composite material and a composite anti-oxidation coating. By adding HfSi2 and ZrSi2 to the coating slurry and introducing a small amount of oxygen during the coating sintering process, HfSi2 and / or ZrSi2 are oxidized in situ to produce SiO2 self-healing phase and expand in volume to fill the pores and cracks in the coating, thereby significantly improving the problems of loose structure, poor bonding between particles, and low interface bonding strength in the ceramic coating prepared by the traditional slurry-sintering process.

[0006] All of the above adopt chemical vapor deposition process, brushing-sintering process, etc. to improve the antioxidant properties of carbon materials. However, these traditional chemical vapor deposition processes and brushing-sintering processes have the problem that the coating material cannot evenly penetrate into the porous structure of the carbon aerogel when used to improve the antioxidant properties of carbon aerogel, and cannot achieve effective carbon aerogel antioxidant properties. There is also a method of liquid phase impregnation, in which silicone oil is used to modify the porous carbon material, and a SiC coating can be obtained after high-temperature pyrolysis. However, during the drying process, there is medium migration in the coating precursor, resulting in uneven coating. At present, the preparation of antioxidant coatings for highly porous carbon materials needs to solve the problem of uniformity. Therefore, it is urgent to develop nanoporous carbon aerogel antioxidant coating technology to meet the application requirements of 1800°C in an aerobic environment. Therefore, it is urgent to improve the existing antioxidant coating process to improve the antioxidant properties of carbon aerogel materials, obtain a high-temperature resistant and antioxidant carbon aerogel material, and provide a new idea for the development of high-temperature thermal protection materials. Summary of the invention

[0007] In order to solve one or more technical problems existing in the prior art, the present invention provides a method for preparing an oxidation-resistant carbon aerogel material in a first aspect, the preparation method comprising the following steps:

[0008] (1) Preparation of borosilicate modified phenolic resin: adding a solvent, a boron-containing modifier and a silicon-containing modifier to a phenolic resin in sequence for esterification reaction, and removing the solvent to obtain a borosilicate modified phenolic resin;

[0009] (2) Preparation of borosilicate modified phenolic aerogel: adding a solvent and a curing agent to the borosilicate modified phenolic resin in sequence to carry out a curing reaction, and then drying to obtain a borosilicate modified phenolic aerogel;

[0010] (3) Preparation of borosilicate modified carbon aerogel: carbonizing the borosilicate modified phenolic aerogel in an inert atmosphere to obtain borosilicate modified carbon aerogel;

[0011] (4) Preparation of SiC inner coating: placing the borosilicate modified carbon aerogel and SiC ceramic precursor solution in a reaction vessel, and depositing the SiC inner coating on the borosilicate modified carbon aerogel with the assistance of supercritical CO2 to obtain a borosilicate modified carbon aerogel containing a SiC inner coating;

[0012] (5) Preparation of ceramic oxygen barrier layer: preparing a Zr-Si ceramic oxygen barrier layer on the borosilicate modified carbon aerogel containing a SiC inner coating by a sol-gel method to obtain a double-coated borosilicate modified carbon aerogel having a SiC inner coating and a Zr-Si ceramic oxygen barrier layer;

[0013] (6) Preparation of SiO2 sealing layer: A SiO2 sealing layer is prepared on the surface of the double-coated borosilicate modified carbon aerogel by a sol-gel method, thereby preparing a carbon aerogel material having a SiC-Zr / Si-SiO2 composite coating.

[0014] In a second aspect, the present invention provides an oxidation-resistant carbon aerogel material prepared by the method described in the first aspect of the present invention.

[0015] Compared with the prior art, the present invention has at least the following beneficial effects:

[0016] (1) For the first time, the matrix modification combined with the skeleton modification technology was used to improve the antioxidant properties of porous carbon aerogel materials. By designing and synthesizing boron silicon and other heteroatom-doped modified phenolic resin as the organic precursor resin for preparing carbon aerogel, the bulk antioxidant properties of carbon aerogel were achieved. Then, supercritical deposition technology combined with sol-gel technology was used to prepare SiC-Zr / Si-SiO2 composite coatings on the three-dimensional nano-skeleton of carbon aerogel to achieve the skeleton antioxidant properties of carbon aerogel, and finally achieve the effect of double protection, significantly improving the antioxidant properties of carbon aerogel materials. The boron silicon heteroatom doping combined with the SiC-Zr / Si-SiO2 composite coating system can achieve effective protection of carbon aerogel materials at a temperature resistance level of 2200℃.

[0017] (2) A ceramic inner coating-ceramic oxygen barrier layer-oxide sealing layer, namely SiC-Zr / Si-SiO2 composite coating system, was designed to make the carbon aerogel material suitable for different service environments. Below 800°C, the silicon-boron modified carbon aerogel inside the carbon aerogel material is distributed more continuously, which can protect the fiber and the matrix. In the low temperature range of 800-1000℃, the oxidation products of Zr are B2O3 and ZrO2, which play a dual role of filling cracks and pores and blocking airflow scouring; at 1000-1400℃, the surface SiO2 and SiO2 generated by oxidation of SiC can flow to form a glass film to fill defects such as cracks and nanopores, and on the other hand, SiO2 can also serve as a sealing glass phase to effectively prevent and slow down the diffusion and penetration of oxygen; at 1400-1800℃, a borosilicate glass self-healing phase is formed in the coating, which effectively fills and heals cracks and pores, slows down the diffusion and penetration of oxygen, and thus improves the oxidation resistance of the material; at 1800℃-2200℃, a large amount of SiO2 glass phase evaporates, and the precipitated ZrO2 gradually sinters densely, which can effectively protect the substrate.

[0018] (3) The introduction of SiC has two effects: First, since the thermal expansion coefficient of SiC is very close to that of carbon materials, designing it as an inner coating can solve the problem of thermal stress matching between the carbon aerogel matrix and the Zr / Si coating and reduce the generation of cracks. In particular, the use of supercritical assisted deposition technology to achieve uniform deposition of SiC on the three-dimensional skeleton of carbon aerogel solves the problem that the coating material cannot uniformly penetrate into the pore structure when preparing coatings by traditional processes such as chemical vapor deposition. Second, the introduction of the second phase SiC in the ceramic oxygen barrier layer can improve the mismatch between the thermal expansion coefficients of the ceramic oxygen barrier layer and the matrix. When oxidized at high temperature, boron-silicon glass with a higher melting point, greater viscosity, lower oxygen diffusion rate and lower vapor pressure is formed on the surface of the material, thereby obtaining an ideal glassy oxygen barrier layer, so that the carbon-based composite material has both good mechanical properties and anti-oxidation and ablation properties. In particular, the use of sol-gel technology to prepare the ceramic oxygen barrier layer solves the problem of uneven coating caused by the migration of the coating precursor medium when preparing the coating by liquid phase impregnation method. The present invention ingeniously uses SiC as the second phase of the inner coating and the ceramic oxygen barrier layer, and adopts supercritical deposition technology combined with sol-gel technology to prepare the SiC inner coating and the ceramic oxygen barrier layer, thereby achieving effective anti-oxidation of the porous carbon aerogel material. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be fully described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] As described above, the present invention provides a method for preparing an oxidation-resistant carbon aerogel material in a first aspect, the preparation method comprising the following steps:

[0021] (1) Preparation of borosilicate modified phenolic resin: adding a solvent, a boron-containing modifier and a silicon-containing modifier to a phenolic resin in sequence for esterification reaction, and removing the solvent to obtain a borosilicate modified phenolic resin;

[0022] (2) Preparation of borosilicate modified phenolic aerogel: adding a solvent and a curing agent to the borosilicate modified phenolic resin in sequence to carry out a curing reaction, and then drying to obtain a borosilicate modified phenolic aerogel;

[0023] (3) Preparation of borosilicate modified carbon aerogel: carbonizing the borosilicate modified phenolic aerogel in an inert atmosphere to obtain borosilicate modified carbon aerogel;

[0024] (4) Preparation of SiC inner coating: placing the borosilicate modified carbon aerogel and SiC ceramic precursor solution in a reaction vessel, and depositing the SiC inner coating on the borosilicate modified carbon aerogel with the assistance of supercritical CO2 to obtain a borosilicate modified carbon aerogel containing a SiC inner coating;

[0025] (5) Preparation of ceramic oxygen barrier layer: preparing a Zr-Si ceramic oxygen barrier layer on the borosilicate modified carbon aerogel containing a SiC inner coating by a sol-gel method to obtain a double-coated borosilicate modified carbon aerogel having a SiC inner coating and a Zr-Si ceramic oxygen barrier layer;

[0026] (6) Preparation of SiO2 sealing layer: A SiO2 sealing layer is prepared on the surface of the double-coated borosilicate modified carbon aerogel by a sol-gel method, thereby preparing a carbon aerogel material having a SiC-Zr / Si-SiO2 composite coating.

[0027] The preferred embodiments of the present invention will be further described in steps below.

[0028] Step (1): Preparation of borosilicate modified phenolic resin

[0029] In this step, a solvent, a boron-containing modifier and a silicon-containing modifier are sequentially added to the phenolic resin to carry out an esterification reaction, and the boron-silicon-modified phenolic resin is obtained after removing the solvent.

[0030] In some preferred embodiments, the boron-containing modifier is any one of boric acid, phenylboric acid and p-hydroxyphenylboric acid.

[0031] In other preferred embodiments, the silicon-containing modifier is any one of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane and ethyl orthosilicate.

[0032] In other preferred embodiments, the solvent is any one of ethanol, ethylene glycol, n-propanol, isopropanol, n-pentanol and butanone.

[0033] In other preferred embodiments, the mass ratio of the phenolic resin, the silicon-containing modifier, the boron-containing modifier and the solvent is 10:(1-4):(0.5-3):(15-100), for example, 10:(1, 2, 3 or 4):(0.5, 1, 1.5, 2, 2.5 or 3):(15, 20, 30, 40, 50, 60, 70, 80, 90 or 100).

[0034] In other preferred embodiments, the esterification reaction is carried out by heating. More preferably, the esterification reaction temperature is 50-150° C. (e.g., 50, 60, 70, 80, 90, 100, 110, 120, 130, 140 or 150° C.), and the reaction time is 5-20 h (e.g., 5, 10, 15 or 20 h).

[0035] Preferably, the solvent removal can be carried out by vacuum distillation. More preferably, the distillation temperature of the vacuum distillation is 40-180° C. (e.g., 40, 50, 80, 100, 120, 150 or 180° C.), the distillation pressure is 100-1000 Pa (e.g., 200, 300, 400, 500, 600, 700, 800, 900 or 1000 Pa), and the distillation time is 0.5-3 h (e.g., 0.5, 1, 2 or 3 h).

[0036] Step (2): Preparation of borosilicate modified phenolic aerogel

[0037] In this step, a solvent and a curing agent are sequentially added to the borosilicate modified phenolic resin to carry out a curing reaction, and then dried to obtain a borosilicate modified phenolic aerogel.

[0038] Preferably, the curing agent is hexamethylenetetramine.

[0039] Preferably, the solvent is any one of ethanol, ethylene glycol, n-propanol, isopropanol, n-pentanol and butanone.

[0040] Preferably, the mass ratio of the curing agent, borosilicate modified phenolic resin and solvent is (2-5):20:(30-180), for example, (2, 3, 4, 5):20:(30, 50, 80, 100, 150 / 180).

[0041] Preferably, the reaction temperature of the curing reaction is 70-140° C. (e.g., 80, 90, 100, 110, 120, 130 or 140° C.) More preferably, the reaction time of the curing reaction is 12-90 h (e.g., 12, 24, 36, 48, 60, 72, 84 or 90 h).

[0042] In this step, the drying method is atmospheric pressure drying or supercritical drying.

[0043] Step (3): Preparation of borosilicate modified carbon aerogel

[0044] In this step, the borosilicate modified phenolic aerogel is carbonized in an inert atmosphere to obtain a borosilicate modified carbon aerogel.

[0045] Preferably, the carbonization is carried out in an inert atmosphere, more preferably, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0046] Preferably, the carbonization temperature may be 800-1400° C. (eg, 800, 900, 1000, 1100, 1200, 1300 or 1400° C.), and the carbonization time may be 0.5-3 h (eg, 0.5, 1, 2 or 3 h).

[0047] Step (4): Preparation of SiC inner coating

[0048] In this step, the borosilicate modified carbon aerogel and SiC ceramic precursor solution are placed in a reaction container, and a SiC inner coating is deposited on the borosilicate modified carbon aerogel with the assistance of supercritical CO2 to obtain a borosilicate modified carbon aerogel containing a SiC inner coating.

[0049] Preferably, the SiC ceramic precursor is polycarbosilane.

[0050] Preferably, the SiC ceramic precursor solution is a mixture of polycarbosilane and a catalyst. More preferably, the catalyst is any one of a platinum catalyst, diisopropylbenzene peroxide, azobisisobutylonitrile and dibenzoyl peroxide.

[0051] Preferably, the mass ratio of the polycarbosilane to the catalyst is 100:(0-5), for example, 100:(0, 1, 2, 3, 4 or 5).

[0052] Preferably, the mass ratio of the SiC ceramic precursor solution to the borosilicate modified carbon aerogel is (1-10):100, for example (1, 2, 3, 4, 5, 6, 7, 8, 9 or 10):100.

[0053] In some particularly preferred embodiments, the deposition is carried out in the following manner: CO2 is charged into the reactor at a pressure increase rate of 100 to 500 kPa / min (for example, 100, 200, 300, 400 or 500 kPa / min), and the SiC ceramic precursor solution in the reactor is stirred at a speed of 300 to 800 rpm (for example, 300, 400, 500, 600, 700 or 800 rpm), and then the temperature in the reactor is raised to 28 to 40°C (for example, 28, 30, 35 or 40°C) at a rate of 2 to 5°C / min (for example, 2, 3, 4 or 5°C / min), so that the CO2 in the reactor reaches a supercritical state, and the SiC ceramic precursor in the reactor is completely dissolved, and the adsorption is achieved after 0.5 to 5h (for example, 0.5, 1, 2, 3, 4 or 5h). After balancing, the reactor is depressurized to atmospheric pressure for 50 to 80 seconds (for example, 50, 60, 70 or 80 seconds) to obtain a carbon aerogel material on which a SiC ceramic precursor is deposited; then the carbon aerogel material on which a SiC ceramic precursor is deposited is cured in a nitrogen or argon atmosphere at 80 to 300° C. (for example, 80, 100, 150, 200, 250 or 300° C.) for 6 to 24 hours (for example, 6, 12, 18 or 2 4h), and then the temperature is increased to 800-1600°C (for example, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500 or 1600°C) at a heating rate of 1-5°C / min (for example, 1, 2, 3, 4 or 5°C / min) and cracked for 0.5 to 5h (for example, 0.5, 1, 2, 3, 4 or 5h) to obtain a borosilicate modified carbon aerogel with a SiC inner coating deposited thereon.

[0054] Step (5): Preparation of ceramic oxygen barrier layer

[0055] In this step, a Zr-Si ceramic oxygen barrier layer is prepared on the borosilicate modified carbon aerogel containing a SiC inner coating by a sol-gel method to obtain a double-coated borosilicate modified carbon aerogel having a SiC inner coating and a Zr-Si ceramic oxygen barrier layer.

[0056] In some particularly preferred embodiments, the Zr-Si ceramic oxygen barrier layer is prepared by: immersing the borosilicate modified carbon aerogel containing the SiC inner coating in a mixed solution containing a Zr precursor and a Si precursor, then curing it in situ, taking it out and drying it, and then performing high-temperature pyrolysis to obtain a carbon aerogel containing a SiC-Zr / Si coating.

[0057] Preferably, the Zr precursor is a ZrC ceramic precursor or a ZrB2 ceramic precursor.

[0058] In addition, preferably, the Si precursor is a SiC ceramic precursor.

[0059] Further preferably, the mixed solution of the Zr precursor and the Si precursor is prepared by dissolving the Zr precursor and the Si precursor in a solvent. Preferably, the solvent is any one of cyclohexane, tetrahydrofuran, butyl ether, cyclopentyl methyl ether, methyl acetate, ethyl acetate and butyl acetate.

[0060] More preferably, the mass ratio of the Zr precursor, the Si precursor, the solvent and the borosilicate modified carbon aerogel containing a SiC inner coating is (2-20):(1-10):(30-50):10, for example, (2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20):(1, 2, 3, 4, 5, 6, 7, 8, 9 or 10):(30, 40, 50):10.

[0061] Preferably, the in-situ curing has a curing pressure of 0.5 to 5 MPa (e.g., 0.5, 1, 2, 3, 4 or 5 MPa), a curing temperature of 80 to 130° C. (e.g., 80, 90, 100, 110, 120 or 130° C.), and a curing time of 8 to 24 h (e.g., 8, 12, 18 or 24 h).

[0062] Preferably, the drying temperature is 50-150° C. (eg, 50, 100 or 150° C.), and the drying time is 10-30 h (eg, 10, 20 or 30 h).

[0063] Preferably, the pyrolysis temperature of the high temperature pyrolysis is 1400-1600°C (for example, 1400, 1500 or 1600°C), the heating rate is 1-5°C / min (for example, 1, 2, 3, 4 or 5°C / min), the pyrolysis time is 1-5h (for example, 1, 2, 3, 4 or 5h), and the pyrolysis atmosphere is argon.

[0064] Step (6): Preparation of SiO2 sealing layer

[0065] In this step, a SiO2 sealing layer is prepared on the surface of the double-coated borosilicate modified carbon aerogel by a sol-gel method, thereby preparing a carbon aerogel material resin having a SiC-Zr / Si-SiO2 composite coating.

[0066] More preferably, the SiO2 sealing layer is prepared by: immersing the double-coated borosilicate modified carbon aerogel in a SiO2 precursor solution, then curing it in situ, taking it out and drying it to obtain a carbon aerogel material with a SiC-Zr / Si-SiO2 composite coating.

[0067] Preferably, the solid content of the SiO2 precursor solution is 5-25% (eg, 5, 10, 15, 20 or 25%).

[0068] Preferably, the mass ratio of the SiO2 precursor solution to the double-coated borosilicate modified carbon aerogel is (10-30):100, for example (10, 20 or 30):100.

[0069] Preferably, the in-situ curing has a curing pressure of 0.5 to 5 MPa (e.g., 0.5, 1, 2, 3, 4 or 5 MPa), a curing temperature of 50 to 100° C. (e.g., 50, 60, 70, 80, 90 or 100° C.), and a curing time of 8 to 24 h (e.g., 8, 12, 18 or 24 h).

[0070] In a second aspect, the present invention provides an oxidation-resistant carbon aerogel material prepared by the preparation method described in the first aspect of the present invention. The oxidation-resistant carbon aerogel material prepared by the method of the present invention has significantly improved antioxidant properties and can be used to prepare heat-insulating materials for use in high-temperature thermal protection.

[0071] Example

[0072] The present invention is further described below in conjunction with the examples. The following examples cannot limit the scope of protection of the present invention, and any improvements made on the basis of the present invention that do not violate the spirit of the present invention are within the scope of protection of the present invention.

[0073] Example 1

[0074] (1) Add 100g of phenolic resin and 900g of anhydrous ethanol to a 1L three-necked flask in turn, and stir to dissolve the phenolic resin. Add 5g of boric acid to the flask, start stirring and heating at the same time, and react at 50°C for 5h. Then add 10g of methyltrimethoxysilane to the flask and heat to react for 5h. After the product is cooled, transfer it to the rotary bottle of a rotary evaporator, and remove the solvent by reduced pressure distillation. Set the distillation temperature to 40°C, the distillation time to 0.5h, and the system pressure to 100Pa to obtain borosilicate-modified phenolic resin.

[0075] (2) Weigh 100 g of the borosilicate modified phenolic resin obtained in step (1), 2 g of hexamethylenetetramine and 600 g of ethanol, stir and mix at room temperature, transfer to a hydrothermal kettle, and cure at 70° C. for 12 h. After curing, take out the borosilicate modified phenolic wet gel in the hydrothermal kettle and dry it at normal pressure to obtain a borosilicate modified phenolic aerogel.

[0076] (3) The borosilicate modified phenolic aerogel obtained in step (2) was transferred to an atmosphere furnace and carbonized at 800° C. for 0.5 h under a nitrogen atmosphere to obtain a borosilicate modified carbon aerogel.

[0077] (4) 1g polycarbosilane and 0.005g platinum catalyst were mixed and stirred to obtain a polycarbosilane solution, which was added to the reactor. Then 99g of carbon aerogel was placed in the reactor and the reactor was tightened. Carbon dioxide was filled into the reactor at a rate of 100kPa / min, and the ceramic precursor solution in the reactor was stirred (300rpm). At the same time, heating was turned on and heated to 28°C at a rate of 2°C / min (referred to as the first heating rate, the same below) to make the carbon dioxide in the reactor reach a supercritical state. After the polycarbosilane in the reactor was completely dissolved, it took 0.5h to reach adsorption equilibrium, and the heating was stopped. The reactor was quickly depressurized to atmospheric pressure within 50s to obtain a carbon aerogel with polycarbosilane deposited. The carbon aerogel was placed in an atmosphere furnace with a nitrogen atmosphere, heated to 80°C at a rate of 1°C / min (referred to as the second heating rate) for curing for 6h, and then heated to 800°C for pyrolysis for 0.5h after the curing was completed to obtain a borosilicate modified carbon aerogel containing a SiC inner coating.

[0078] (5) Weigh 20g of ZrC ceramic precursor, 10g of SiC ceramic precursor and 300g of cyclohexane and mix them well. Place 100g of carbon aerogel with SiC inner coating deposited in a mold and seal it. Inject the mixed solution of ceramic precursors into the mold, apply a pressure of 0.5MPa to the mold, and cure it at 100℃ for 8h. After the mold cools down, take out the carbon aerogel and let it air at room temperature, and then dry it at 100℃ for 10h. Then, pyrolyze the carbon aerogel in a nitrogen atmosphere at 1400℃ for 1h to obtain a carbon aerogel containing SiC-ZrC / SiC coating.

[0079] (6) The carbon aerogel with SiC-ZrC / SiC coating deposited in step (5) is placed in a mold and sealed. 10 g of SiO2 precursor solution with a solid content of 5% is injected into the mold, a pressure of 0.2 MPa is applied to the mold, and the mold is cured at 50°C for 5 hours. The carbon aerogel is taken out and dried at room temperature to obtain a carbon aerogel containing SiC-ZrC / SiC-SiO2 coating.

[0080] (7) Material performance test: The above materials were subjected to an isothermal static firing experiment at 1600°C in a muffle furnace, and the appearance, size and weight before and after static firing were recorded. After the material was isothermal static fired at 1600°C for 2 hours, the appearance was intact without cracks, the shrinkage rate in the thickness direction was 3%, and the residual weight was 95%. The above materials were subjected to oxyacetylene assessment tests at 1800°C and 2200°C (the assessment time was 1500s), and the appearance, linear ablation rate and mass ablation rate before and after the assessment were recorded. After the above materials were subjected to oxyacetylene assessment at 1800°C, the surface layer partially turned white, and the linear ablation rate was 5.34×10 -5 mm / s, and the mass ablation rate is 8.68×10 -6 After the above material was tested with oxyacetylene at 2200℃, the surface layer turned partially white, and the linear ablation rate was 9.41×10 -4 mm / s, and the mass ablation rate is 8.02×10 -5 g / s.

[0081] Examples 2 to 6

[0082] The preparation was carried out in substantially the same manner as in Example 1, except for the differences shown in Tables 1 to 5.

[0083] Comparative Example 1

[0084] This comparative example provides a method for preparing a conventional carbon aerogel, and the specific steps are as follows:

[0085] (1) Weigh 100 g of phenolic resin, 2 g of hexamethylenetetramine and 600 g of ethanol, stir and mix at room temperature, transfer to a hydrothermal autoclave, and cure at 70° C. for 12 h. After the curing is completed, take out the phenolic wet gel in the hydrothermal autoclave and dry it at normal pressure to obtain a phenolic aerogel.

[0086] (2) The phenolic aerogel prepared in step (1) was transferred to an atmosphere furnace and carbonized at 800° C. for 0.5 h under a nitrogen atmosphere to obtain a carbon aerogel.

[0087] Comparative Example 2

[0088] The method is basically the same as that of Example 1, except that step (4), step (5) and step (6) in Example 1 are not performed.

[0089] Comparative Example 3

[0090] The method is basically the same as that of Example 1, except that step (5) and step (6) in Example 1 are not performed.

[0091] Comparative Example 4

[0092] The method is basically the same as that of Example 1, except that step (4) in Example 1 is not performed.

[0093] Comparative Example 5

[0094] The method is basically the same as that of Example 1, except that step (5) in Example 1 is not performed.

[0095] Comparative Example 6

[0096] The method is basically the same as that of Example 1, except that step (6) in Example 1 is not performed.

[0097]

[0098]

[0099]

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an oxidation-resistant carbon aerogel material, characterized in that: The preparation method comprises the following steps: (1) Preparation of borosilicate modified phenolic resin: adding a solvent, a boron-containing modifier and a silicon-containing modifier to a phenolic resin in sequence for esterification reaction, and removing the solvent to obtain a borosilicate modified phenolic resin; (2) Preparation of borosilicate modified phenolic aerogel: adding a solvent and a curing agent to the borosilicate modified phenolic resin in sequence to carry out a curing reaction, and then drying to obtain a borosilicate modified phenolic aerogel; (3) Preparation of borosilicate modified carbon aerogel: carbonizing the borosilicate modified phenolic aerogel in an inert atmosphere to obtain borosilicate modified carbon aerogel; (4) Preparation of SiC inner coating: placing the borosilicate modified carbon aerogel and SiC ceramic precursor solution in a reaction vessel, and depositing the SiC inner coating on the borosilicate modified carbon aerogel with the assistance of supercritical CO2 to obtain a borosilicate modified carbon aerogel containing a SiC inner coating; (5) Preparation of ceramic oxygen barrier layer: preparing a Zr-Si ceramic oxygen barrier layer on the borosilicate modified carbon aerogel containing a SiC inner coating by a sol-gel method to obtain a double-coated borosilicate modified carbon aerogel having a SiC inner coating and a Zr-Si ceramic oxygen barrier layer; (6) Preparation of SiO2 sealing layer: A SiO2 sealing layer is prepared on the surface of the double-coated borosilicate modified carbon aerogel by a sol-gel method, thereby preparing a carbon aerogel material having a SiC-Zr / Si-SiO2 composite coating.

2. The preparation method according to claim 1, characterized in that: In step (1): The boron-containing modifier is any one of boric acid, phenylboric acid and p-hydroxyphenylboric acid; The silicon-containing modifier is any one of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane and ethyl orthosilicate; The solvent is any one of ethanol, ethylene glycol, n-propanol, isopropanol, n-pentanol and butanone; and / or The mass ratio of the phenolic resin, the silicon-containing modifier, the boron-containing modifier and the solvent is 10:(1-4):(0.5-3):(15-100).

3. The preparation method according to claim 1 or 2, characterized in that: In step (1): The esterification reaction is carried out by heating; preferably, the temperature of the esterification reaction is 50-150°C and the reaction time is 5-20h; Preferably, the solvent is removed by vacuum distillation; more preferably, the vacuum distillation has a distillation temperature of 40-180°C, a distillation pressure of 100-1000 Pa, and a distillation time of 0.5-3h.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (2): The curing agent is hexamethylenetetramine; The solvent is any one of ethanol, ethylene glycol, n-propanol, isopropanol, n-pentanol and butanone; The mass ratio of the curing agent, borosilicate modified phenolic resin and solvent is (2-5):20:(30-180); The reaction temperature of the curing reaction is 70 to 140°C; The curing reaction time is 12 to 90 hours; and / or The drying method is atmospheric pressure drying or supercritical drying.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (3): The carbonization is carried out in an inert atmosphere, preferably, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; The carbonization temperature of the carbonization is 800-1400° C., and the carbonization time is 0.5-3 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that In step (4): The SiC ceramic precursor is polycarbosilane; The SiC ceramic precursor solution is a mixture of polycarbosilane and a catalyst, and the catalyst is any one of a platinum catalyst, diisopropylbenzene peroxide, azobisisobutyronitrile and dibenzoyl peroxide; The mass ratio of the polycarbosilane to the catalyst is 100:(0-5); and / or The mass ratio of the SiC ceramic precursor solution to the borosilicate modified carbon aerogel is (1-10):

100.

7. The preparation method according to any one of claims 1 to 6, characterized in that In step (4): The deposition is carried out in the following manner: CO2 is charged into the reactor at a pressure increase rate of 100 to 500 kPa / min, and the SiC ceramic precursor solution in the reactor is stirred at a speed of 300 to 800 rpm, and then the temperature in the reactor is increased to 28 to 40°C at a rate of 2 to 5°C / min, so that the CO2 in the reactor reaches a supercritical state, and after the SiC ceramic precursor in the reactor is completely dissolved and reaches adsorption equilibrium after 0.5 to 5 hours, the reactor is depressurized to atmospheric pressure after 50 to 80 seconds to obtain a carbon aerogel material with a SiC ceramic precursor deposited thereon; and then the carbon aerogel material with the SiC ceramic precursor deposited thereon is cured at 80 to 300°C for 6 to 24 hours under a nitrogen or argon atmosphere, and then the temperature is increased to 800-1600°C at a heating rate of 1 to 5°C / min and cracked for 0.5 to 5 hours to obtain a borosilicate modified carbon aerogel with a SiC inner coating deposited thereon.

8. The preparation method according to any one of claims 1 to 7, characterized in that In step (5): The Zr-Si ceramic oxygen barrier layer is prepared by: dipping the borosilicate modified carbon aerogel containing the SiC inner coating in a mixed solution containing a Zr precursor and a Si precursor, then in-situ curing, taking out and drying, and then performing high-temperature pyrolysis to obtain a carbon aerogel containing a SiC-Zr / Si coating; The Zr precursor is a ZrC ceramic precursor or a ZrB2 ceramic precursor, and the Si precursor is a SiC ceramic precursor; The mixed solution of the Zr precursor and the Si precursor is prepared by dissolving the Zr precursor and the Si precursor in a solvent, wherein the solvent is any one of cyclohexane, tetrahydrofuran, butyl ether, cyclopentyl methyl ether, methyl acetate, ethyl acetate and butyl acetate; The mass ratio of the Zr precursor, the Si precursor, the solvent and the borosilicate-modified carbon aerogel containing the SiC inner coating is (2-20):(1-10):(30-50):10; The curing pressure of the in-situ curing is 0.5-5 MPa, the curing temperature is 80-130° C., and the curing time is 8-24 hours; The drying temperature of the drying is 50-150°C and the drying time is 10-30h; The pyrolysis temperature of the high temperature pyrolysis is 1400-1600° C., the heating rate is 1-5° C. / min, the pyrolysis time is 1-5 hours, and the pyrolysis atmosphere is argon.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (6): The SiO2 sealing layer is prepared by: dipping the double-coated boron-silicon modified carbon aerogel in a SiO2 precursor solution, then in-situ curing, taking out and drying, to obtain a carbon aerogel material with a SiC-Zr / Si-SiO2 composite coating; The solid content of the SiO2 precursor solution is 5 to 25%; The mass ratio of the SiO2 precursor solution to the double-coated borosilicate modified carbon aerogel is (10-30):100; and / or The in-situ curing has a curing pressure of 0.5 to 5 MPa, a curing temperature of 50 to 100° C., and a curing time of 8 to 24 hours.

10. An oxidation-resistant carbon aerogel material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of low-temperature long-time oxidation-resistant coating layer on carbon / carbon composite material surfaces

    CN105646007A

  • Method for improving sintering density of anti-oxidation coating on surface of carbon-based or ceramic-based composite material and composite anti-oxidation coating

    CN116082065A

  • Compact high-temperature anti-oxidation coating on surface of carbon-based or ceramic-based composite material and preparation method of compact high-temperature anti-oxidation coating

    CN116375504A

  • High-temperature-resistant SiC-zirconium dioxide ceramic aerogel heat-insulation composite material as well as preparation method and application thereof

    CN107778006A

  • Heat-resistant phenolic aerogel and preparation method thereof

    CN111234299A

Cited By

  • Multilayer antioxidant carbon aerogel composite material and preparation method and application thereof

    CN122233819A

  • Preparation method and application of porous composite phase change heat storage material

    CN122587666A